Bovine campylobacteriosis in bulls: insights in the conventional and molecular diagnosis - García, Juan Agustín; Farace, Pablo Daniel; Gioffre, Andrea; Morsella, Claudia Graciela; Mendez, Maria Alejandra; Acuña, Joaquín; Aller Atucha, Juan Florencio; Signorini Porchiett, Marcelo Lisandro; Paolicchi, Fernando (Springer Nature, 2023)
Campylobacter fetus is a gram-negative motile bacterium, with two subspecies relevant to cattle health: C. fetus subsp. venerealis (Cfv) and C. fetus subsp. fetus (Cff). Both subspecies are associated with reproductive losses in cattle. In this study, we evaluated the identification of C. fetus for the diagnosis of bovine campylobacteriosis through bacteriological culture, direct immunofluorescence (DIF) and molecular tests in preputial smegma (PS) samples of three Angus bulls challenged with Cfv, Cfv biovar intermedius (Cfvi) or Cff, respectively, in an experiment imitating the natural infection. Two DNA extraction protocols were tested (in-house thermal extraction and commercial kit). Aspiration and scraping collection for PS were compared by conventional tests. Additionally, bacteremia was also evaluated in blood samples. Bulls were challenged by natural mating with heifers that had been experimentally infected with C. fetus subspecies; which led to infection. The Cfv- and Cfvi-bulls were positive for at least 9 months. Although Cff is not considered a venereal strain, in this study it was transmissible to bull from heifers experimentally infected, as evidenced by its colonization and persistence in the preputial cavity for 5 to 6 months. This finding suggests a potential risk of dissemination within herds. The results obtained by bacteriological culture or direct immunofluorescence (DIF) showed no significant differences, regardless the sampling device used (aspiration with Cassou pipette, metal and plastic scraper). C. fetus qPCR, on the other hand, yielded better results with an in-house DNA extraction method than with a commercial kit (75% vs 66.6%). Furthermore, qPCR diagnosis was more efficient than culture (66.6%) or DIF (56%). Bacteremia in whole blood samples was negative by qPCR and bacteriological culture in all samples. Altogether, this study demonstrated the transmission of Cff from heifers to bull and also showed that PCR-based methods are promising for the diagnosis of Bovine Genital Campylobacteriosis from clinical samples of PS.